2011
DOI: 10.1097/nen.0b013e3182275264
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Virologic Characterization of Neuroinvasion by HSV-2 in a Mouse Encephalitis Model

Abstract: Herpes simplex virus type 2 (HSV-2), a ubiquitous human pathogen associated with genital infections, is neurotropic. It establishes latent infections in local dorsal root ganglia from which it reactivates causing recurrent lesions and frequent episodes of viral shedding. Herpes simplex virus type 2 can also be transmitted from mother to child during birth, causing major neonatal complications including encephalitis. Animal models of HSV-2 genital infection are well described and used for testing of therapies; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…HSV-1 showed a strong predominance of TG over OB involvement. Immunostaining also showed much more TG and brainstem infection than OB infection in infant mice (data not shown), consistent with previous reports (16, 17, 38, 39). …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…HSV-1 showed a strong predominance of TG over OB involvement. Immunostaining also showed much more TG and brainstem infection than OB infection in infant mice (data not shown), consistent with previous reports (16, 17, 38, 39). …”
Section: Resultssupporting
confidence: 92%
“…Others have found this for lytic infection (47), and the lack of a viral Cre recombinase footprint in floxed reporter gene mice showed that most i.n.-infected mice lack even latent OB infection. OB involvement seems to occur mainly in severe infections, for example, in juvenile mice, and even then later and less consistently than TG involvement (17, 38), suggesting that secondary virus spread, from meninges (48), bloodstream (39), or other brain regions, is more common than direct passage along olfactory neurons. Vomeronasal organ involvement (49) may similarly reflect secondary spread during severe infection, as our milder i.n.…”
Section: Discussionmentioning
confidence: 99%
“…6e), neuroinvasion along OSN projections is thought to be utilized by several neurotropic viruses [2,11,39]. The present study demonstrates that LACV utilizes transport along OSN pathways when administered i.n.…”
Section: Discussionmentioning
confidence: 77%
“…Many neurotropic viruses were shown to reach the central nervous system after interacting with the nasal mucosa in animal models, including MHV (Perlman et al., 1989), the Borna disease virus (BDV) (Shankar et al., 1992), the pseudorabies virus (PrV)(Babic et al., 1994), the herpes simplex virus type 1 and 2 (HSV‐1/HSV‐2)(Allavena et al., 2011; Barnett et al., 1993), the human coronavirus OC43 (HCoV‐OC43) (St‐Jean et al., 2004) and adenovirus (Lemiale et al., 2003). After infecting the OE, the vesicular stomatitis virus VSV can spread along the olfactory nerves into the glomeruli of the OBs, and afterwards, progressively spread to the brain (Lundh et al., 1987).…”
Section: Invasion Of the Central Nervous System Through The Olfactory Routementioning
confidence: 99%